Luigi Nono et les chemins de l'écoute: Entre espace qui sonne et espace du son : Une analyse de No hay caminos Hay que caminar... Tarkovskij, per 7 cori (1987) - Leblanc, Jimmie (Paris L'Harmattan, 2010)
Luigi Nono (1924-1990), a Venetian composer and one of the most influential figures in twentieth-century music, continues to fuel reflection not only on musical practice but also on the relationship between art and humanity. This analysis of "No hay caminos Hay que caminar... Tarkovskij" is based on the idea that the work not only updates the composer's thinking in terms of compositional methods, but also constitutes an application of that thinking in terms of perception. (Translated with Deepl.com)
Keywords: Nono, Luigi -- 1924-1990; Musical analysis